2019
DOI: 10.1001/jamaophthalmol.2018.6367
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Clinical Follow-up and Genetic Spectrum of Patients With Rod-Cone Dystrophy Associated With Mutations inPDE6AandPDE6B

Abstract: IMPORTANCE A precise phenotypic characterization of retinal dystrophies is needed for disease modeling as a basis for future therapeutic interventions. OBJECTIVE To compare genotype, phenotype, and structural changes in patients with rod-cone dystrophy (RCD) associated with mutations in PDE6A or PDE6B. DESIGN, SETTING, AND PARTICIPANTS In a retrospective cohort study conducted in Paris, France, from January 2007 to September 2017, 54 patients from a cohort of 1095 index patients with RCD underwent clinical exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
37
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 62 publications
8
37
3
Order By: Relevance
“…Nevertheless, this ellipsoid has been observed to progressively evolve into a uniformly round shape, which occurs due to a difference in the rate of one ring diameter's constriction compared to that of the other diameter. In our study, we found a faster rate of progression for the horizontal diameter in comparison to the vertical (Table 5), which is in accordance with the findings in the literature [26,27]. Thus, it is expected that the horizontal diameter would have a better correlation with ERG as opposed to the vertical diameter of the hyperfluorescent ring, due to the faster progression of the former.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, this ellipsoid has been observed to progressively evolve into a uniformly round shape, which occurs due to a difference in the rate of one ring diameter's constriction compared to that of the other diameter. In our study, we found a faster rate of progression for the horizontal diameter in comparison to the vertical (Table 5), which is in accordance with the findings in the literature [26,27]. Thus, it is expected that the horizontal diameter would have a better correlation with ERG as opposed to the vertical diameter of the hyperfluorescent ring, due to the faster progression of the former.…”
Section: Discussionsupporting
confidence: 92%
“…The mean age at diagnosis was 27.5 years (range, 11-60 years) in our cohort. This is similar to that reported in a previous study of RP associated with mutations in the PDE6 gene family (21.0 years; range, 3-45 years) 12 ; however, it is much lower than the mean age at diagnosis reported in a study examining all types of RP in patients of Korean ethnicity (44.8 years; range, 0-95 years) 13 . Considering the age of disease onset, the patients with PDE6B variants in our study experienced their first ocular symptoms at a median age of 10.0 years; this is relatively early compared to the median age of onset reported in a previous study of RP associated with other causative genes (29 years; range, 4-77 years) 14 .…”
Section: Discussionsupporting
confidence: 88%
“…Among the PDE6B variants identified in this study, c.1669C > T was the most common, followed by c.1604T > A. Both variants have been commonly reported in a database of PDE6B mutations 24 , but the frequency of variants in our study was notably different to that observed in European patients 12 . Correlating characteristic phenotypes with PDE6B variants, we found that CME is frequently found in patients with the c.1669C > T variant.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Mutations in the gene encoding the beta subunit of rod cGMP-phosphodiesterase type 6 (PDE6B) account for 4 to 5% of autosomal recessive RP (Danciger et al, 1995). Recently, PDE6B mutation was identified as disease-causing gene in 2.4% patients from a large cohort of 1095 patients with RP (Khateb et al, 2019). Prevalent mouse models harboring Pde6b mutations, rd1, and rd10 have been widely used for deciphering pathogenesis and examining novel therapeutics for RP (Bowes et al, 1990; Barhoum et al, 2008).…”
Section: Introductionmentioning
confidence: 99%